Grèzes litées and their genesis: the site of Enscherange in the Rhenish-Ardennes Massif as a case study - Nyssen, Jan; Van Nieuland, Jasper; Vandenberghe, Dimitri; Juilleret, Jérôme; Terhorst, Birgit (DIE ERDE: Journal of the Geographical Society of Berlin, 2016)
The freeze-thaw cycles in periglacial areas during the Quaternary glacials increased frost weathering, leading to a disintegration of rock formations. Transported downslope, clasts allowed in some areas the formation of stratified slope deposits known as “grèzes litées”. This study reviews the existing theories and investigates the grèzes litées deposits of Enscherange and Rodershausen in Luxembourg. This process was reinforced by the lithostructural control of the parent material expressed by the dip of schistosity (66°) and its orientation parallel to the main slopes in the area. This gave opportunities to activate the frost-weathering process on top of the ridge where the parent material outcropped. As the stratified slope deposits have a dip of 23° and as there is no significant lateral variation in rock fragment size, slope processes that involve only gravity are excluded and transportation in solifluction lobes with significant slopewash and sorting processes is hypothesized. The Enscherange formation, the biggest known outcrop of grèzes litées in north-western Europe, shows evidence of clear layering over the whole profile depth. A palaeolandscape reconstruction shows that ridges must have been tens of metres higher than presently. The investigation of the matrix composition shows Laacher See tephra in the overlying periglacial cover bed with infiltrations of the minerals in the reworked upper layer of the grèzes litées deposit. Chronostratigraphic approaches using the underlying cryoturbation zone and Laacher See heavy minerals in the overlying topsoil place the formation of grèzes litées deposits in the Late Pleistocene.